'Anuş̄on nūang nai ngān phrarātchathān phl̄œng sop Khunying Lēkhā 'Aphaiwong, Tḩ̄o. Cḩ̄o. Tḩ̄o. M̧̄o. . (s.n.,] P̧̄o Samphan Phānit, 1983)
Cremation volume for Lēkhā 'Aphaiwong, 1906-1983, wife of Khūang 'Aphaiwong, 1902-1968, former prime minister of Thailand; comprises an autobiography in manuscript form, genealogy of the crematee, condolences, and a lecture on his life by Khūang 'Aphaiwong.